2018
DOI: 10.1177/1177271918792244
|View full text |Cite
|
Sign up to set email alerts
|

Is Procalcitonin Useful in Pediatric Critical Care Patients?

Abstract: This review examines the use of procalcitonin in different clinical situations in the pediatric patient, with special emphasis on those requiring intensive care. We review the latest articles on its potency as a biomarker in both infectious processes at diagnosis and on the response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 110 publications
(119 reference statements)
0
12
0
Order By: Relevance
“…Much like for adults, sepsis is one of the most researched conditions for the use of PCT-guided antibiotic therapy in children. Other potential diseases include bacterial infection [ 135 ], where a recent review reported reduced antibiotic exposure and length of ICU stay [ 136 ], as well as bronchiolitis [ 137 ] and meningitis [ 107 ], all of which showed promising results.…”
Section: Department Of Pediatricsmentioning
confidence: 99%
“…Much like for adults, sepsis is one of the most researched conditions for the use of PCT-guided antibiotic therapy in children. Other potential diseases include bacterial infection [ 135 ], where a recent review reported reduced antibiotic exposure and length of ICU stay [ 136 ], as well as bronchiolitis [ 137 ] and meningitis [ 107 ], all of which showed promising results.…”
Section: Department Of Pediatricsmentioning
confidence: 99%
“…Its early response to an active infection and its rapid drop when the infection is controlled help clinicians to stop or curtail antibiotic therapy. Its use is widely recognised in infants with fever of unknown origin [11][12][13], as it is a more accurate biomarker than traditional screening tests [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies underlined the promising utility of them as prognostic predictors in patients with heart failure or low cardiac output syndrome also in children [69]. PCT is known to be more specific and earlier than classical biomarkers in the diagnosis of infectious complications [10,11]. Although PCT may increase slightly in the systemic inflammatory response syndrome, as it occurs after CPB, most studies point to better predictive values of PCT than other clinical or analytical markers to discriminate the presence or absence of infection [6,1214].…”
Section: Introductionmentioning
confidence: 99%